Integrated management of water resources and demand in the touristic area of Saint-Tropez in a drought context - Jose-Maria F. (Drought management: scientific and technological innovations, 2008)
The SIDECM Syndicate is in charge of water supply in France's touristic Mediterranean area of Saint- Tropez, which has experienced high growth in consumption. Confronted with severe drought spates, the Syndicate has set up the following management capabilities: (i) factoring in climatic changement; (ii) preserve the upstream downstream balance of the flux resource; and (iii) act on both supply and demand to maintain such equilibrium. The key actions on supply consisted of: (i) diversifying and protecting the supply sources; and (ii) devising predictive resource management tools. The demand-side actions are four-pronged: (i) progressive pricing; (ii) regular information campaigns toward the users; (iii) education and cooperation actions; and (iv) a pilot economy-seeking operation.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)